Personality and Organization Structure: Staff Models and Behavioral Patterns - Golembiewski, Robert T. (Academy of Management Journal, 1966)
Students of organization long have raised questions about orthodox line-staff arrangements in organizations, but little of the literature is consciously oriented toward the testing of hypotheses necessary to support the development of an alternate model of relations. The following article begins the necessary scientific dialetic in reporting the method and results of a pilot study. Despite the limitations of the data, the results are consistent and of significant interest. The data from a more elaborate research design applied to a larger sample are in the early stages of processing. Thus far, they support the pattern outlined here. The follow-up design also seeks related covariants in small groups and in such characteristics of individuals as ordinal position of siblings in their families.